PENGARUH DIGITAL MARKETING DAN BRAND IMAGE TERHADAP INTENSI PEMBELIAN PRODUK KECANTIKAN EMINA - Rika hasanah; Siti maryam (Jurnal Publikasi Manajemen Informatika, 2024)
Technological advances sharpen competition in the beauty industry and force companies to always innovate to remain competitive. This research aims to analyze digital marketing and brand image on purchasing intentions for Wardah Beauty products. This research uses a survey research model. The research results show that digital marketing and brand image have a significant effect on purchasing intentions. This research also proves that digital-based marketing activities through social media are very effective. This research only focuses on two variables, namely digital marketing and brand image.